2013
DOI: 10.1074/jbc.m113.507210
|View full text |Cite
|
Sign up to set email alerts
|

Serum- and Glucocorticoid-induced Protein Kinase 1 (SGK1) Is Regulated by Store-operated Ca2+ Entry and Mediates Cytoprotection against Necrotic Cell Death

Abstract: Background: Mechanisms underlying SGK1 activation are incompletely understood in epithelial cells. Results: Store-operated Ca 2ϩ entry up-regulates SGK1, thereby modulating the lethal effects of Ca 2ϩ overloading on mitochondrial membrane potential. Conclusion: Ca 2ϩ -induced SGK1 activates cytoprotective signaling and modifies mitochondrial function in epithelial cells. Significance: This work reveals a cytoprotective role for SGK1 in necrosis and has potential relevance for epithelial cell protection and can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 65 publications
0
19
0
Order By: Relevance
“…Given that Akt does not appear to be a relevant mediator of ATP generation downstream of PI(3)K (in the presence of oncogenic Ras) during ECM detachment, we assessed the contribution of SGK-1, another AGC family kinase known to operate downstream of PI(3)K. 6 SGK-1 shares significant sequence identity with Akt and has previously been linked to the regulation of glucose transporter localization. 6,[18][19][20] In our 10A HrasG12V and 10A KrasG12V cells, we see a decrease in SGK-1 activation upon PI(3)K inhibition as measured by phosphorylation status of Sek1 at serine 80 (Figure 1e), a canonical downstream SGK-1 target. 21 In addition, we observe an increase in the phosphorylation of Sek1 in the presence of oncogenic Ras mutations (Figure 1f).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Given that Akt does not appear to be a relevant mediator of ATP generation downstream of PI(3)K (in the presence of oncogenic Ras) during ECM detachment, we assessed the contribution of SGK-1, another AGC family kinase known to operate downstream of PI(3)K. 6 SGK-1 shares significant sequence identity with Akt and has previously been linked to the regulation of glucose transporter localization. 6,[18][19][20] In our 10A HrasG12V and 10A KrasG12V cells, we see a decrease in SGK-1 activation upon PI(3)K inhibition as measured by phosphorylation status of Sek1 at serine 80 (Figure 1e), a canonical downstream SGK-1 target. 21 In addition, we observe an increase in the phosphorylation of Sek1 in the presence of oncogenic Ras mutations (Figure 1f).…”
Section: Resultsmentioning
confidence: 97%
“…34 It is noteworthy that other investigators have discovered that SGK-1 can interact with proteins at the mitochondria and can inhibit the induction of necrotic cell death. 19,35 Our data implicating SGK-1 in ATP generation may provide additional insight into these connections between SGK-1 and mitochondrial integrity.…”
Section: Discussionmentioning
confidence: 99%
“…As 1 subunit of ICRAC, Ca 2+ release‐activated Ca 2+ channel protein 1 (Orai1) was identified as being coexpressed with SGK1 protein in human endometrium and Ishikawa cells (73). Furthermore, SGK1 boosts SOCE activity by up‐regulating its pore‐forming subunit and its regulators Orai1/stromal interacting molecule 1 via phosphorylation and inactivation of the ubiquitin ligase neuronal precursor cell‐expressed, developmentally down‐regulated 4 ligase, which ubiquitinates Orai1 (73, 74), thereby mediating cellular Ca 2+ entry upon stimulation of multiple mitogenic factors‐aprerequisite for triggering cell proliferation (25, 69, 75, 76). Moreover, SGK1 invokes activation of NF‐κB, a transcription factor that is required for Orai1 and Orai1/stromal interacting molecule 1 transcription (73, 74).…”
Section: Involvement Of Sgk1 In Decidualizationmentioning
confidence: 99%
“…Moreover, SGK1 invokes activation of NF-kB, a transcription factor that is required for Orai1 and Orai1/stromal interacting molecule 1 transcription (73,74). Of interest, Brickley et al (76) suggested that the increasing influx of extracellular Ca 2+ through I CRAC up-regulates SGK1 transcription in human mammary epithelial cells, which, in turn, attenuates mitochondrial membrane hyperpolarization and subsequent cell death induced by Ca 2+ overloading. This positive feedback accentuates the effects of SGK1 on cell proliferation and survival.…”
Section: Sgk1 Promotes Cell Proliferation and Survival Of Deciduamentioning
confidence: 99%
“…SGK-1 belongs to the AGC kinase family and is the sole C. elegans homologue of the mammalian Serum-and Glucocorticoid-inducible Kinase. Its expression is induced upon diverse stimuli, including overload of calcium [16], heat shock, oxidative or osmotic stress [1719], besides of glucocorticoids, cytokines and growth factors [20, 21]. Its activation is dependent on PI3K and has been involved in response to oxidative stress and DNA damage, among others [22].…”
Section: Introductionmentioning
confidence: 99%